2013
DOI: 10.1073/pnas.1309010110
|View full text |Cite
|
Sign up to set email alerts
|

Public goods dilemma in asexual ant societies

Abstract: Cooperation in biological, social, and economic groups is underpinned by public goods that are generated by group members at some personal cost. Theory predicts that public goods will be exploited by cheaters who benefit from the goods by not paying for them, thereby leading to the collapse of cooperation. This situation, described as the "public goods dilemma" in game theory, makes the ubiquity of cooperation a major evolutionary puzzle. Despite this generalization, the demonstration of genetic background and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 66 publications
2
47
0
Order By: Relevance
“…HRIs usually do not forage and contribute little to cooperative tasks, and colonies with higher proportions of HRIs might therefore be less efficient at raising offspring. This interpretation is in line with findings in the thelytokous ant Pristomyrmex punctatus, in which colonies with a higher proportion of 'cheaters', which behave similar to C. biroi HRIs in that they reproduce more but don't contribute to cooperative tasks, have lower fitness 39 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…HRIs usually do not forage and contribute little to cooperative tasks, and colonies with higher proportions of HRIs might therefore be less efficient at raising offspring. This interpretation is in line with findings in the thelytokous ant Pristomyrmex punctatus, in which colonies with a higher proportion of 'cheaters', which behave similar to C. biroi HRIs in that they reproduce more but don't contribute to cooperative tasks, have lower fitness 39 .…”
Section: Discussionsupporting
confidence: 89%
“…Individuals of this cheater lineage, which like C. biroi HRIs do not forage, have more ovarioles and lay more eggs than average individuals [29][30][31]50 . As mentioned above, a recent study showed that, in mixed colonies, the P. punctatus cheater lineage performs better than host workers, both in terms of survival and reproduction, while its fitness in isolation is greatly reduced 39 . The P. punctatus cheater lineage is an obligate social parasite, that is, it has lost the phenotypic plasticity that would allow it to function in isolation.…”
Section: Discussionmentioning
confidence: 87%
“…Theory and experimental evidence indicates that an optimal division of labour for the group can be undermined by the selfishness of individuals (Dobata & Tsuji, ). In eusocial insects, for example, workers behave selfishly by laying unfertilized eggs that develop into males (Visscher, ; Foster & Ratnieks, ; Halling et al ., ), actions that are deleterious to the group because they divert time and energy away from raising the offspring of the queen (Cole, ; Hammond & Keller, ).…”
Section: Introductionmentioning
confidence: 99%
“…But as cheating becomes more common, the benefits of cooperating (and hence, the benefits of associating with the group) diminish, and more cooperative groups outcompete groups with more free-riders (e.g. [21]). Thus, the solution to the game is a stable equilibrium frequency of each tactic, potentially explaining how variation in cooperative behaviour is maintained in natural populations.…”
Section: Introductionmentioning
confidence: 99%